Consideration of Sex as a Biological Variable in the Development of Doxorubicin Myotoxicity and the Efficacy of Exercise as a Therapeutic Intervention - Ryan N. Montalvo; Vivian Doerr; Branden L. Nguyen; Rachel C. Kelley; Ashley J. Smuder (MDPI AG, 2021)
Doxorubicin (DOX) is an anthracycline antibiotic used to treat a wide variety of hematological and solid tumor cancers. While DOX is highly effective at reducing tumor burden, its clinical use is limited by the development of adverse effects to both cardiac and skeletal muscle. The detrimental effects of DOX to muscle tissue are associated with the increased incidence of heart failure, dyspnea, exercise intolerance, and reduced quality of life, which have been reported in both patients actively receiving chemotherapy and cancer survivors. A variety of factors elevate the probability of DOX-related morbidity in patients; however, the role of sex as a biological variable to calculate patient risk remains unclear. Uncertainty regarding sexual dimorphism in the presentation of DOX myotoxicity stems from inadequate study design to address this issue. Currently, the majority of clinical data on DOX myotoxicity come from studies where the ratio of males to females is unbalanced, one sex is omitted, and/or the patient cohort include a broad age range. Furthermore, lack of consensus on standard outcome measures, difficulties in long-term evaluation of patient outcomes, and other confounding factors (i.e., cancer type, drug combinations, adjuvant therapies, etc.) preclude a definitive answer as to whether differences exist in the incidence of DOX myotoxicity between sexes. This review summarizes the current clinical and preclinical literature relevant to sex differences in the incidence and severity of DOX myotoxicity, the proposed mechanisms for DOX sexual dimorphism, and the potential for exercise training to serve as an effective therapeutic countermeasure to preserve muscle strength and function in males and females.